Pengaruh Penyuluhan terhadap Pengetahuan dan Sikap 5R (Ringkas, Rapi, Resik, Rawat, Rajin) pada Tenaga Kerja di Sentra Industri Pengrajin Blangkon Serengan Surakarta - Muslihah, Muslihah, Tarwaka, PGDip Sc, M.Erg, Sri Darnoto, SKM, MPH (2016)
The application of 5C be applied throughout the industrial sector, both formal and informal industry. Lack of information on 5C in the industrial sector informal impact on the lack of knowledge and attitude 5C on workers. The purpose of this research was to analyze the influence of councelling to knowledge and attitude about 5C on mployee's blangkon industry centre, Serengan Surakarta. This research's method used quasi experimental by one group pretest and posttest. The population in this research was blangkon craftsman employee's about 88 workers. The sample technique used proportional sampling technique as many as 47 respondents. The result of this research showed an increase in the average score at the knowledge before and after treatment as many as 44.2 %. In the attitude showed an increase in the average score before and after treatment as many as 54.3 %. The results of statistical tests used wilcoxon on knowledge shows p value 0.000 and in the attitude of shows p value 0.000 wich mean ≤ 0.05, so it can be concluded that there is influence of counselling to the knowledge and attitude about 5C on employee's blangkon industry centre, Serengan Surakarta. The advice to employee's is to be more enterprising in the tracery of related information about 5C so can be applied 5C at work place and to the government to conduct counselling further so that employee's can understand more about the purposes of 5C. Keywords : Councelling, 5C ( Clear-out, Configure, Clean, Conform, Custom ), Knowledge, Attitude.